Ecuador, deuda externa e inversión privada, periodo 1990-2020. - Rios Amaya, Christian Steven (My University, 2021)
It is an important issue to analyze the effect caused by the growth of foreign debt in an economy, since Ecuador maintains a problem of fiscal deficit due to the high growth of foreign debt, this has attracted the attention of many academics who wonder which one is the impact of external debt on investment in the private sector and GDP, the present research aims to identify the ratio of external debt to investment and GDP, estimating the co-integration of variables model where it can be possible to identify if the variables have some kind of short-term or long-term relationship, the results show that the variables have a relationship only in the long term, but not in the short term, that is, their short-term relationship is inverse, it is concluded that in a Debt growth causes a minimal growth effect on short-term private investment.
Es un tema importante analizar el efecto que causa el crecimiento de la deuda externa en una economía, ya que el Ecuador mantiene un problema de déficit fiscal por el alto crecimiento de la deuda externa, esto ha llamado la atención de muchos académicos que se preguntan cuál es el impacto de la deuda externa sobre la inversión en el sector privado y el PIB, la presente investigación tiene como objetivo identificar la relación de la deuda externa sobre la inversión y el PIB, haciendo una estimación de modelo de coitegracion de variables donde se podrá identificar si las variables tienen algún tipo de relación a corto plazo o a largo plazo, los resultados muestran que las variables tienen relación solo a largo plazo, pero no a corto plazo, es decir su relación a corto plazo es inversa, se concluye que en un crecimiento de la deuda causa un efecto de crecimiento mínimo en la inversión privada a corto plazo.
Keywords: COITEGRACION; EFECTO; INVERSIÓN; FLUCTUACIONES